2020
DOI: 10.1016/j.psychres.2020.113128
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia during COVID-19 pandemic and lockdown: Prevalence, severity, and associated risk factors in French population

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
173
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(201 citation statements)
references
References 9 publications
(12 reference statements)
17
173
3
8
Order By: Relevance
“…Poor quality sleep due to COVID-19, however, remained a significant risk for loneliness. This is in line with studies in Greece and France that have reported sleep problems are common during this pandemic, and that loneliness is a major contributor to insomnia [79,80]. Indeed, sleep problems have recently been proposed as a mechanism of the relationship between loneliness and health [81].…”
Section: Covid-19 Specific Factorssupporting
confidence: 90%
“…Poor quality sleep due to COVID-19, however, remained a significant risk for loneliness. This is in line with studies in Greece and France that have reported sleep problems are common during this pandemic, and that loneliness is a major contributor to insomnia [79,80]. Indeed, sleep problems have recently been proposed as a mechanism of the relationship between loneliness and health [81].…”
Section: Covid-19 Specific Factorssupporting
confidence: 90%
“…Poor quality sleep due to COVID-19, however, remained a significant risk for loneliness. This is in line with studies in Greece and France that have reported sleep problems are common during this pandemic, and that loneliness is a major contributor to insomnia (Kokou-Kpolou et al, 2020;Voitsidis et al, 2020). Indeed, sleep problems have been proposed as a mechanism of the relationship between loneliness and health (Griffin et al, 2020).…”
Section: Covid-19 Specific Factorssupporting
confidence: 90%
“…Sleep habits were previously proposed as lifestyle factors that could be an important component of mental health during lockdown [ 22 ]. We observed that most individuals reported longer and shifted sleeps.…”
Section: Discussionmentioning
confidence: 99%